Unveiling the oxidation mechanism of CrTaTiMo refractory medium-entropy alloys: a synergy of density functional theory and ab initio molecular dynamics - Wang, Xiao (2024)
The demand for advanced materials capable of withstanding extreme high-temperature conditions has led to the development of novel High-Entropy Alloys (HEAs). Recent works indicate that forming a CrTaO4 protection layer gives HEAs excellent long-term oxidation resistance. In this study, the high-temperature oxidation resistance properties of CrTaTiMo Refractory Medium-Entropy Alloys (RMEAs) were assessed by Density Functional Theory (DFT) and ab initio Molecular Dynamics (AIMD). Through the oxygen adsorption and diffusion calculations, we demonstrated the preferential oxygen adsorption sequence on the surface of the RMEA as Ti, Ta, Cr, and Mo. Furthermore, our analysis identified the sites featuring Ta as subsurface atoms were the weakest locations for oxygen atom diffusion. The dynamic oxidation mechanism of oxygen molecules on CrTaTiMo RMEA was investigated by AIMD simulations. The results confirmed that the adsorption and dissociation of O2 molecules on the alloy surface. Additionally, the diffusion of the O atom took place at temperatures greater than 873 K and confirmed the O-attracting feature of Ta atoms. Moreover, electronic structure calculations confirmed the bonding of oxygen atoms with those four metal elements. This study could serve as a valuable reference for the strategic development of the CrTaTiMo-based RMEAs or RHEAs for high-temperature, long-term oxidation resistance applications.